DEVELOPMENT OF HEAVY INDUSTRIES IN THE SOUTHERN PROVINCE OF UZBEKISTAN: HISTORICAL ANALYSIS AND CONSEQUENCES (1930-1960) - Mamatqulov Bekzod Sherozovich (TADQIQOTLAR, 2025)
ABSTRACT: In this article, the development of heavy industries in the southern regions of Uzbekistan, conflicting situations in the process of training industry personnel are analyzed historically based on scientific sources.